Controlled clinical trials of cell therapy in stroke: Meta-analysis at six months after treatment. Issue 7 (October 2017) - Detante, Olivier; Moisan, Anaïck; Hommel, Marc; Jaillard, Assia
Background: Cell therapy is promising in experimental studies and has been assessed only in a few studies on humans. Aims: To evaluate the effect of cell therapy in humans. Methods: We included clinical trials with a control group that reported safety and efficacy six months following treatment. Quality was evaluated and clinical scales data were extracted. Quantitative analysis was based on the standardized means difference (SMD). Among 28 trials published from 1995 to 2016, nine studies (194 patients; 191 controls) were eligible. Publication biases were assessed with the funnel plot and pre-specified explanatory variables were tested with a group analysis and a meta-regression. Results: The overall quality was moderate. Cell therapy had a positive effect on the outcome (SMD: 0.57, 95% CI: 0.22–0.92; p = 0.002). The sensitivity analysis showed an upper level of effect size of 0.81 (95% CI: 0.34–1.27; p = 0.001) and a lower level of 0.455 (95% CI: 0.04–0.87; p = 0.03). None of the pre-specified explanatory variable was significantly correlated to outcome: age, ratio infarction/hemorrhage, delay from stroke to treatment, route of administration, cell type, randomization, and blinded outcome assessment. The significant heterogeneity (p = 0.03) was not explained by publication biases (p = 0.09) and was more likely due to methodological and quality differences between the trials. Conclusions: This result suggests that cell therapy is beneficial in stroke and is expected to help in the designing of stem cells controlled clinical trials (CCT) in large populations.